A Strategy toward the Biomimetic Synthesis of (±)-Morusalbanol A Pentamethyl Ether - Tee, Jia Ti; Keane, Theo; Meijer, Anthony J. H. M.; Khaledi, Hamid; Rahman, Noorsaadah Abd; Chee, Chin Fei (Synthesis, 2016)
A strategy toward the biomimetic synthesis of morusalbanol A pentamethyl ether is described. The synthesis is based on a hydrogen-bond-assisted Diels–Alder cycloaddition between a dehydroprenyl diene and a chalcone dienophile. Selective cleavage of the ortho-methyl ether of the resulting cycloadduct allows rotation of the C3–C21 bond and subsequent intramolecular cyclization affords the pentamethyl ether of (±)-morusalbanol A. As with the natural product, morusalbanol A, a number of key proton and carbon signals are absent in the NMR spectra of the title product.
Keywords: morusalbanol A; Diels–Alder reaction; mulberry; Morus alba; biomimetic synthesis; natural products